DEVELOPMENT OF AN AYURVEDIC DUAL-FORMULATION: SESAMOEUC RELIEF OIL AND OINTMENT FOR ANALGESIC AND ANTI-INFLAMMATORY THERAPY - Pol, Saurbh S; Phulwale, Omkar U; Sabale, Bhakti Y; Sanap, Harshada M; Dhale, Chaitali (International Journal of Pharma and Bio Sciences, 2025)
SesamoEuc Relief Oil is an Ayurvedic blend that includes sesame oil, eucalyptus oil, clove oil, lavender oil, wintergreen oil, and peppermint oil, recognized for their anti-inflammatory, analgesic, and antimicrobial effects. Although the oil allows for quick absorption and penetrates deep into the tissue, its liquid form restricts retention duration, making it essential to create an ointment formulation for extended effect. The ointment was formulated with petroleum jelly, beeswax, glycerin, and borax, creating a semi-solid texture for regulated release and improved skin adhesion. Physicochemical assessment validated stability and purity, exhibiting an acid value <2.0 mg NaOH/g and specific gravity (0.90-0.95 g/mL), thereby guaranteeing formulation uniformity. Sensory evaluation revealed a delightful herbal, minty, and camphor-like scent, accompanied by a non-greasy, quick-absorbing consistency. Microbial testing verified that there was no contamination, ensuring its safety for topical application. The ointment showed better retention and prolonged therapeutic effects, whereas the oil displayed quicker penetration and prompt relief. Bioactivity research demonstrated encouraging anti-inflammatory and antimicrobial properties, validating the oil and ointment as effective solutions for alleviating pain and promoting muscle relaxation. The findings indicate that dual-formulation treatment can improve patient adherence and therapeutic advantages, providing a natural substitute for synthetic pain medications. Additional clinical validation is suggested to evaluate their long-term effectiveness and safety.